The Impact Presence Of The Jelok Tuntang Hydroelectric Power Plant (PLTA) On Community Welfare And Local Ecological Conditions - Hilya Naura Madania; Ingrat Wahyu Wijaya Sembiring; Raesita Lusstie Maharani; Tarlika Yuliyanti; Wina Merli Mualifah; Yuniar Fahmi Lathif (Jurnal Saintifik (Multi Science Journal), 2026)
This study aims to evaluate the impact of the Jelok Tuntang Hydroelectric Power Plant (PLTA) on local residents. The use of hydropower through PLTA is an important alternative amidst increasing energy demand and the issue of dependence on fossil fuels, while supporting the provision of clean, stable, and sustainable energy. The Jelok PLTA, which has been operating since 1938 and is administered by PT Indonesia Power, is located in Delik Village, Tuntang District, Semarang Regency. The methods used in this study include field observations, in-depth interviews with residents, and a literature review to gain a comprehensive understanding of its impacts. The results obtained indicate that the presence of the Jelok Tuntang PLTA has made a significant positive contribution to the social, economic, and infrastructure welfare of the local community. These positive impacts include the provision of regular social assistance such as rice and basic necessities, financial support for business development for MSMEs, and job creation in the area. In addition, the hydroelectric power plant also contributes to the provision of clean water through special filtration facilities, lighting for public facilities such as mosques and village roads, and improving the quality of access roads to the hydroelectric power plant. According to information obtained from informants, no significant negative impacts were found. Overall, the Jelok Tuntang hydroelectric power plant has been proven to improve the quality of life of the community, strengthen its role as strategic infrastructure in the village, and demonstrate significant benefits for the community and village government